Penerapan Metode Inkuiri dan Reciprocal Teaching untuk Meningkatkan Kemampuan Berpikir Siswa Kelas V MI Wahid Hasyim III Malang - Siti Zubaidah; - Chairuddin; Uswatul Khasanah (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: Based on our observation to students and discussion with the principal and the science teacher of Madrasah Ibtidaiyah Wahid Hasyim III (MIWH III) on June, 2, 2006, known that there were complicated problems in science class V. The core of those problems was the most of the student ability to think was still lower, therefore, in this research we want to try to solve the problems by classroom action research (CAR). Some studies shown that applying inquiry-based and reciprocal teaching methods have many advantages to solve the problems like at MIWH III Malang, therefore these methods was applied in this school. The research was conducted during 10 months, start at April until November 2007. This research design was Kemmis and of Taggart model, which consist of four phases. The result of this research showed that implementation of inquiry-based and reciprocal teaching methods improved the student ability to think and learning activities at science class V MIWH III Malang.